Physiological and Morphological Parameters of Middle-Distance Runners - Elkuliyeva Feruza Dilmurod qizi (International Journal of Formal Education, 2024)
Physical education and sports are rapidly developing in our country today. In this article, the physiological and morphological indicators of middle-distance runners in athletics are presented